111 Highly efficient multiplexed base editing enables development of universal CD7-targeting CAR-T Cells to treat T-ALL. (9th November 2020) - Gehrke, Jason; Edwards, Aaron; Murray, Ryan; Messana, Angelica; Coholan, Lindsey; Poulin, Henry; Le, Melissa; Ladd, Alden; Naniong, Mark; Musenge, Faith; Camblin, Adam; Poh, Yeh-Chuin; et al.
Abstract : Background: Autologous CAR-T therapies have demonstrated remarkable efficacy in treating some hematologic cancers. However, generating bespoke cell therapies creates manufacturing challenges, inconsistent products, high cost of goods, and delays in treatment that are often incompatible with effective clinical management of patients. Strategies to create universally-compatible allogeneic CAR-T therapies have been developed as a solution to these challenges. Allogeneic CAR-Ts require mitigation of graft-versus-host-disease (GvHD), host rejection of CAR-Ts, and elimination of fratricide in instances where the target (e.g. CD7) is expressed on both malignant cells and healthy T-cells. Many allogeneic CAR-T approaches utilize DNA double strand break (DSB)-inducing nucleases to overcome these barriers. However, simultaneous induction of multiple DSBs results in unpredictable outcomes such as large-scale genomic rearrangements, megabase-scale deletions, and reduced cell proliferation. Here we leverage base editors (BEs), which are a novel class of gene editing reagents that enable programmable single-base changes in genomic DNA without forming DSBs, to create multiplex edited, fratricide resistant, allogeneic CAR-T cells with no detectable genomic aberrations. Methods: T-cell acute lymphoblastic leukemia (T-ALL) is a disease with high and consistent expression of CD7 on malignant T cells, making CD7-targeting CAR-Ts (7CAR-Ts) an attractive therapeutic agent. We developed a GMP-compatible process to create 7CAR-Ts at clinical scale by isolating T cells from healthy human donors and electroporating the cells with base editor reagents, followed by transduction with a lentiviral vector encoding a second generation anti-CD7 CAR. 7CAR-Ts were characterized for their potency and specificity in vitro and in xenograft tumor models. Results: Simultaneous base editing at four genomic loci resulted in 7CAR-Ts that are edited with 80–98% efficiency at each target gene, with greatly diminished risk of GvHD, CAR-T rejection, fratricide, and immunosuppression. In contrast to nuclease editing, concurrent modification of four genomic loci using BEs produced no detectable genomic rearrangements, no observable change in cell expansion, and no activation of the DNA damage-induced p53 pathway. Base edited 7CAR-Ts demonstrate robust antigen-dependent cytokine release, potent in vitro cytotoxicity, and dose-dependent in vivo tumor control. Conclusions: Taken together, our approach addresses limitations in CAR-T manufacturing and demonstrates that multiplexed base editing is a feasible strategy for generating universally-compatible, fratricide-resistant 7CAR-T cells, which we are advancing towards clinical development for the treatment of T-ALL. More generally, this program demonstrates the potential for base editing to create highly-engineered cell therapies featuring at least four simultaneous edits which can confer a wide range of desirable therapeutic attributes.